Chlorin-e6 conjugated to the antimicrobial peptide LL-37 loaded nanoemulsion enhances photodynamic therapy against multi-species biofilms related to periodontitis - Garcia de Carvalho, Gabriel [UNESP]; Maquera-Huacho, Patricia Milagros [UNESP]; Silva Pontes, Cristiano [UNESP]; Annunzio, Sarah Raquel de [UNESP]; Fontana Mendonça, Carla Raquel [UNESP]; Nara de Souza Rastelli, Alessandra [UNESP]; de Oliveira, Kleber Thiago; Teughels, Wim; Chorilli, Marlus [UNESP]; Leal Zandim-Barcelos, Daniela [UNESP]; Palomari Spolidorio, Denise Madalena [UNESP] (Elsevier, 2023)
In our previous studies, Chlorin-e6 (Ce6) demonstrated a significant reduction of microorganisms' viability against multi-species biofilm related to periodontitis while irradiated with blue light. However, the conjugation of Ce6 and antimicrobial peptides, and the incorporation of this photosensitizer in a nanocarrier, is still poorly explored. We hypothesized that chlorin-e6 conjugated to the antimicrobial peptide LL-37 loaded nanoemulsion could inhibit a multi-species biofilm related to periodontitis during photodynamic therapy (PDT), the pre-treatment with hydrogen peroxide was also tested. The nanoemulsion (NE) incorporated with Ce6 was characterized regarding the physiochemical parameters. Images were obtained by transmission electron microscopy (TEM) and scanning electron microscopy (SEM). Later, the Ce6 and LL-37 incorporated in NE was submitted to UV-Vis analysis and Reactive Oxygen Species (ROS) assay. Finally, the combined formulation (Ce6+LL-37 in nanoemulsion) was tested against multi-species biofilm related to periodontitis. The formed nanoformulation was kinetically stable, optically transparent with a relatively small droplet diameter (134.2 unloaded and 146.9 loaded), and weak light scattering. The NE system did not impact the standard UV-VIS spectra of Ce6, and the ROS production was improved while Ce6 was incorporated in the NE. The combination of Ce6 and LL-37 in NE was effective to reduce the viability of all bacteria tested. The treatment with hydrogen peroxide previous to PDT significantly impacted bacterial viability. The current aPDT regimen was the best already tested against periodontal biofilm by our research team. Our results suggest that this combined protocol must be exploited for clinical applications in localized infections such as periodontal disease. - Nanoemulsion demonstrated to be an excellent nanocarrier for photodynamic application. - Chlorin-e6 incorporated in nanoemulsion showed great physicochemical and biophotonic parameters. - The combination of chlorin-e6 and LL-37 peptide in nanoemulsion is effective to eliminate periodontal pathogenic bacteria. - The treatment with hydrogen peroxide previous to PDT significantly impacted bacterial viability.